2013
DOI: 10.1371/journal.pone.0083368
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Panton-Valentine Leukocidin mRNA among Staphylococcus aureus Isolates Associates with Specific Clinical Presentations

Abstract: Panton-Valentine leukocidin (PVL; gene designation lukF/S-PV) is likely an important virulence factor for Staphylococcus aureus (S. aureus), as qualitative expression of the protein correlates with severity for specific clinical presentations, including skin and soft tissue infections (SSTIs). Development of genetic approaches for risk-assessment of patients with S. aureus infections may prove clinically useful, and whether lukF/S-PV gene expression correlates with specific clinical presentations for S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Regarding lukF gene, it was not expressed by any of the tested isolates. This was in accordance with a study by Yu et al (2013) reporting that the PVL detected by qRT-PCR was expressed in all isolates harboring PVL genes by variable levels suggesting that PVL genes transcription is associated with clinical isolates. Another study showed that PVL genes expression levels are strain dependent, with more than 10-fold variance (Said-Salim et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding lukF gene, it was not expressed by any of the tested isolates. This was in accordance with a study by Yu et al (2013) reporting that the PVL detected by qRT-PCR was expressed in all isolates harboring PVL genes by variable levels suggesting that PVL genes transcription is associated with clinical isolates. Another study showed that PVL genes expression levels are strain dependent, with more than 10-fold variance (Said-Salim et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The only 3 cases of omphalitis we observed (caused by Staphylococcus aureus) were in the dry care group, but they were easily managed, including the case that presented with Panton-Valentine Leukocidin toxin, which is usually associated with serious bacterial infection. 16 The most frequent bacterium cultured from the umbilical cord was S aureus, as previously described in high-income countries. 4,17,18 In all isolated bacteria, no resistance to usual antibiotic treatment was observed.…”
Section: Discussionmentioning
confidence: 82%
“…PVL is a biocomponent synergohymenotropic cytotoxin associated with furunculosis, severe necrotizing hemorrhagic pneumonia, necrotizing fasciitis and other lesions involving the skin and mucosa. [ 15 ] The gene encoding PVL is frequently found in CA-MRSA strains carrying SCCmec -IV. [ 16 ] Since the PVL gene is known to be associated with virulence,[ 17 ] determining the presence of the PVL gene in MRSA strains might be important to early and proper therapy for serious MRSA infections.…”
Section: Resultsmentioning
confidence: 99%